Pengaruh Motivasi Kerja, Self-Efficacy dan Lingkungan Kerja Non Fisik terhadap Kepuasan Kerja Karyawan PT. Alsafwa Bahanan Turindo Surabaya - Mohamad Andre; Bowo Santoso (J-MAS (Jurnal Manajemen dan Sains), 2022)
Employees have an important role in achieving company goals. However, the smoothness of work is determined by the level of employee job satisfaction with the field in which they are engaged in the company. But in reality the company still has problems such as absenteeism that goes up and down due to dissatisfaction experienced by employees. This study aims to determine the effect of work motivation, self-efficacy and non-physical work environment on employee job satisfaction at PT Alsafwa Bahanan Turindo Surabaya. The research method used in this research is quantitative with questionnaires to answer the research problem formulation. The population in this study were employees of PT. Alsafwa Bahanan Turindo Surabaya, which amounted to 53 people, which of that number was also the overall sample of the study. While the analytical tool used is Partial Least Square (PLS). The results of the analysis state that: 1) work motivation is inversely proportional to job satisfaction; 2) self-efficacy is not able to support job satisfaction; and 3) non-physical work environment is not able to support job satisfaction.